HAMBATAN EKSPORTIR KOPI SUMSEL MELAKUKAN PENETRASI PASAR LUAR NEGERI (Studi Kasus PT Inti Baru Sejati ) - Markoni Badri (Politeknik Negeri Sriwijaya, 2012)
The research is aimed to analyze the barriers of coffee exporter in penetrating foreign market, especialy German and United States market. It is merely case study whereas the research are mainly focus on PT Inti Baru Sejati as one of South Sumatera coffee expoter. The main problems in this research are as follows. Firstly, what are the barriers of PT Inti Bari Sejati in penetrating German and United State market. Secondly, what are the efforts of PT Inti Baru Sejati to overcome the barriers of penetrating foreign market, especially for German and United State market. Primary data are used in this research by depth interview to the owner and some staffs of company. It is also used secondary data to enrich the research analysis. The research finding shows that some entry barriers in penetrating both countries are the difference business cultures, administrative business requirement, product quality standard, tariff and non-tariff barries, lacking of business information as well as international marketing system. The research conclusion indicates that PT Inti Baru Sejati should learn and understand foreign market, especially German and United State market, therefore PT Inti Baru Sejati should adjust its marketing strategy to overcome the entry barriers in both countries.